The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/hel.12927
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and risk of multiple sclerosis: An updated meta‐analysis

Abstract: Background There is considerable controversy around the question as to whether Helicobacter pylori (H. pylori) infection has a protective or causative role in the development of multiple sclerosis (MS). This study evaluated published information to assess the association between H. pylori infection and MS. Methods We conducted a comprehensive systematic review of relevant observational studies in international databases. A random‐effects model was used to calculate pooled odds ratio (OR) and 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Income, educational and economic situation, and environmental health factors are differences between developing and developed countries (45). A previous systematic review and meta-analysis by Arjmandi et al investigated the association between HP and MS recently (15). They found that there was no protective effect for HP against MS which depends on diagnostic tests also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Income, educational and economic situation, and environmental health factors are differences between developing and developed countries (45). A previous systematic review and meta-analysis by Arjmandi et al investigated the association between HP and MS recently (15). They found that there was no protective effect for HP against MS which depends on diagnostic tests also.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Neurology Letters. 2023; 2: e2 Neurology Letters│www.neurologyle ers.com between HP and MS, but we believed that a new study with a better methodology is required (15). Hence, we aimed to perform a comprehensive systematic review and meta-analysis to investigate the association between the risk of MS and HP infection.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Helicobacter pylori ( H. pylori ) infection consists one of the most common chronic infections since it affects more than 50% of the world population [ 22 ]. Emerging evidence supports its involvement in the pathophysiology of many neurodegenerative disorders [ 21 , 23 , 24 , 25 , 26 , 27 , 28 ]. Specifically, found in gastric mucosa of ≥50% of humans worldwide, H. pylori can infect children, becoming chronic during adulthood if untreated; in most patients, H. pylori infections are acquired in childhood and, if untreated, persist throughout life [ 29 ], causing the chronic inflammatory process of the stomach lining and leading to many gastric as well as other upper and lower gastrointestinal and extra-gastrointestinal pathologies [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equivalent data may also be obtained for clinically isolated syndrome - multiple sclerosis sequence [ 25 , 28 , 130 ]. Indeed, our studies show that active H. pylori infection, apart from multiple sclerosis [ 28 , 130 ], is also common in clinically isolated syndrome, a prodromic condition predisposing for subsequent development of multiple sclerosis, accompanied by increased homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation